2018
DOI: 10.1039/c8ra06805d
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of chemical warfare agents over cotton fabric functionalized with UiO-66-NH2

Abstract: We develop a very efficient modification method of cotton fabric to be functionalized with a MOF via mercerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 53 publications
(74 reference statements)
1
44
0
Order By: Relevance
“…In contrast, little decomposition of GB and GD was observed with beta-ZTC. To detect the reaction products using GC-MS, the solutions were treated with N,O-bis(trimethylsilyl)trifluoroacetamide, which resulted in the hydrogen atoms of the hydroxyl groups being replaced with trimethylsilyl (TMS) groups [49,50]. Figure S2a,b show the GC spectra and Figure S3a-c show the MS spectra of the reaction products from GB and GD degradation.…”
Section: Degradation Rates and Reaction Products Of Nerve Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, little decomposition of GB and GD was observed with beta-ZTC. To detect the reaction products using GC-MS, the solutions were treated with N,O-bis(trimethylsilyl)trifluoroacetamide, which resulted in the hydrogen atoms of the hydroxyl groups being replaced with trimethylsilyl (TMS) groups [49,50]. Figure S2a,b show the GC spectra and Figure S3a-c show the MS spectra of the reaction products from GB and GD degradation.…”
Section: Degradation Rates and Reaction Products Of Nerve Agentsmentioning
confidence: 99%
“…In the previous section, the performance of the UiO-66-NH 2 /ZTC composites for nerve agent degradation was revealed. UiO-66-NH 2 can provide sites for both adsorption and decomposition via hydrolysis [13,49]. To clarify the effect of beta-ZTC in the U 0.8 Z 0.2 composites, a gas adsorption test was performed.…”
Section: Adsorption Of Nerve Agentsmentioning
confidence: 99%
“…13,14 Among Zr-MOFs, it is worth noting that UiO-66 and its analogs exhibit excellent thermal and chemical stability as well as superior CWAs adsorption and decomposition efficiencies. [15][16][17] For CWA removal, the humidity emerges as an unavoidable challenge that significantly affects the performance of MOFs. 18,19 In the presence of water, adsorbate could diffuse to active sites of MOFs and limit the rate of subsequent reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed investigations were also available regarding the hydrolysis mechanism of sarin, a CWA belonging to the G series of nerve agents, catalyzed by Zr‐based MOFs 13,14 . Among Zr‐MOFs, it is worth noting that UiO‐66 and its analogs exhibit excellent thermal and chemical stability as well as superior CWAs adsorption and decomposition efficiencies 15‐17 …”
Section: Introductionmentioning
confidence: 99%
“…An Aerosol Vapour Liquid Assessment Group (AVLAG) test cell is used to measure the level of CWA permeation through the fabric. For example, the permeation of HD and GD through UiO-66-NH 2 deposited on cotton fibres (16 and 5 μg cm −2 for HD and GD, respectively) resulted to be substantially hindered compared with pure cotton fibres (184 and 120 μg cm −2 for HD and GD, respectively) 114 . Even though previously discussed studies have shown that UiO-66-NH 2 can degrade CWA simulants, amine-functionalized MOFs tend to behave differently when in powder form or when integrated in fabric material.…”
Section: Chemical Toxins and Their Remediationmentioning
confidence: 99%